Epigenetic mechanisms in the development of psychiatric disorders - Erol, Deniz; Elyas, Zeynep; Unal, Suheyla (Kure Iletisim Grubu A S, 2010)
Epigenetics is defined as the study of heritable changes of gene function that occur without a change in the nucleotide sequence of DNA. Aberrant epigenetic mechanisms have been directly implicated in certain human diseases. There is much evidence that epigenetic regulation is involved in neurogenesis, neuronal plasticity, learning and memory, and in psychiatric disorders such as depression, addiction, schizophrenia, and cognitive dysfunction. In this review, the epigenetics mechanisms and their role in the development of psychiatric disorders were discussed.
Psikiyatrik hastaliklarin gelişiminde epigenetik mekanizmalar
Keywords: Psychiatric disorders; epigenetics; chromatin structure